Strategies for Optimizing Land and Building Tax Revenue in Karawang Regency - Frestya Kristyana Carry; Dedi Budiman Hakim; A Faroby Falatehan (Cakrawala Repositori IMWI)
Land and building tax (PBB) is a significant source of regional revenue, yet its realization in Karawang Regency remains low with declining taxpayer compliance. This research aims to describe PBB revenue, determine the level of taxpayer compliance, analyze the influence of the number of taxpayers, compliance rate, PBB receivables, population, and population density on PBB revenue, and formulate alternative strategies for optimizing PBB revenue in Karawang Regency. Primary data were obtained through interviews and questionnaires, while secondary data were derived from documents at relevant agencies. The analytical approaches used include descriptive analysis, panel data regression analysis, and multicriteria policy analysis (MULTIPOL). The results show that the majority of sub-districts in Karawang Regency have very low PBB revenue realization achievement with an average below 50% and tending to decline until 2024, with the compliance ratio decreasing from 38.00% in 2020 to 29.54% in 2024. The panel data regression analysis results indicate that simultaneously the variables of number of taxpayers, compliance rate, PBB receivables, population, and population density have a significant influence on PBB revenue realization, but only the number of taxpayers, compliance rate, and PBB receivables have a significant partial influence. Based on the MULTIPOL analysis with two scenarios, the results show that technology enhancement is the priority policy that must be implemented to optimize PBB revenue, followed by apparatus human resource development, database updating, regulatory availability, and increasing taxpayer awareness.